ORAL REHABILITATION AND SPECIFIC PROTECTIVE MEASURES AGAINST SARS-VOC 2 INFECTION IN DENTAL MEDICINE - Mihaela Cezarina Mehedinți; Mădalina Matei; Moroianu Marius; Buga Vladimir; Trifautanu Petru; Kamel Earar (Romanian Journal of Oral Rehabilitation, 2020)
Oral rehabilitation consists in diagnosing and treating the entire pathology in the oral cavity, in the joint, muscle, bone, by correcting changes caused by tooth loss, abrasions, dental malpositions or the removal of tumors from the face. . S ARS-COV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) belongs to the Coronaviridae family, the beta-coronavirus group. In December 2019, a 2019-nCoV coronavirus (SARS-CoV-2) was discovered in Wuhan, China, which causes severe pneumonia with high mortality; called coronaviruses, which are transmitted directly by the respiratory tract (by drops) or fecal / oral. There is no one specific or preventive antiviral treatment (vaccine) in human coronavirus infections, the treatment being only symptomatic. The pneumonia caused by the new coronavirus was initially detected in the city of Wuhan in Hubei Province and then spread to three other provinces in China: Guangdong Sheng, Beijing Shi and Shanghai Shi. Coronavirus is a group of zoonotic viruses that are part of the coronaviride family and can be transmitted from animal to human, some being asymptomatic and others very aggressive and invasive. The symptoms of coronavirus are similar to those of flu and cold, but they become very aggressive, causing a type of pneumonia that can lead to death in people with low immunity, who have associated diseases, are elderly or in pregnant women.